The Knowledge and Experience of Dengue Mosquitoes among Housewives - Aryani Pujiyanti; Atik Triratnawati (Makara Journal of Health Research, 2011)
Dengue Hemorrhagic Fever (DHF) prevention programs in Semarang, were focused through controlling mosquito breeding sites (PSN), but the implementation of PSN was not become a habit in every household. The objective of this study was to explore knowledge and experience of dengue mosquitoes among housewives in the endemic villages.The research was using qualitative methods. Subjects of the study were 17 housewives which selected by purposive sampling. The data collection was carried in Sendangmulyo village, Semarang, through observation, focus groups discussions, and indepth interviews. The techniques used to test data validity were triangulation and member checking method. Data were analyzed using content analysis approached. The results showed that housewives classifying mosquito based on time occurrence whether the presence of mosquito in environment was perceived naturally. Unoptimalized PSN behavior was based on the lack of housewives knowledge on larvae development stages. Mosquito was not considered as a threatening because night mosquito biting was directly more disturbing rather than day mosquitoes'. Health promotion program could increase dasa wisma cadres knowledge and skill, particularly on mosquito life cycle and the correct stages of PSN behavior. This study did not distinguish the demographic characteristics of informants. Further reserch could explore it or develop media based on local knowledge and experience.